Internet of things security vulnerabilities and recommended solutions - F.Olanrewaju, Rashidah; Ul Islam Khan, Burhan; Anwar, Farhat; Naaz Mir, Roohie (International Journal of Engineering and Technology, 2019)
The applications based on IoT are ubiquitous in providing passive user involvement on the collective approach of sensor technology, embedded system, networking and communication convergence with analytical computing. The application framework of IoT comprises of devices that are highly heterogeneous and compute migrations from sensor to IoT gateways to edge/fog computing to the cloud and then back to the client along with various alarming components. As observed from the review work, providing security for such networks is in its young stage in the form of an integrated architecture offering perfect security together with network and application possibilities although the shortcomings of IEFT and IEEE contribute more towards the same. Besides, the present researchers have not yet achieved the actual threshold of real-time performance potentials with respect to lesser computational complexity, usage of smaller key size, conformable security, lesser memory overheads, smaller ciphertext size, speedy processing time of algorithms, robust to possible threats and reduced communication/network overhead for ensuring a lighter security mechanism. This paper focusses on the security issues posed by large-scale heterogeneous IoT paradigm and arriving at a secure architectural framework adoptable by a variety of applications that include smart transportation, smart cities, smart healthcare, etc. based on IoT.
Keywords: Internet of Things (IoT); IoT Security; Authentication; Key Management; Signcryption.